If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+1)-2(x+1)=2x+10
We move all terms to the left:
3(x+1)-2(x+1)-(2x+10)=0
We multiply parentheses
3x-2x-(2x+10)+3-2=0
We get rid of parentheses
3x-2x-2x-10+3-2=0
We add all the numbers together, and all the variables
-1x-9=0
We move all terms containing x to the left, all other terms to the right
-x=9
x=9/-1
x=-9
| 0.5(x+20)=2+0.75(x−2) | | 6n=246 | | 8x=4=68 | | 1/6(12x-18)=2x=3 | | 16-4n=12 | | 8x+4=98 | | (5x+16)+90+100+102=180 | | Y=5.2(8-y) | | -2z-0z=-21 | | 6x−35+3x+35=180 | | 5t+5t=6-16 | | m/2+-4=-3 | | 2x+5+3x=4-(x-4) | | 12=3(d-14) | | 3v-(2.34)=9.57 | | 4x-2/3=-6x+1/7 | | 3x-2x+6=22 | | 17=j/13 | | -65-x=-4x+22 | | 6-2k-7=3 | | 3y+5=7y-31 | | Y=-11/2x-29 | | 17=4j+31 | | -90=-5v+5(7v-6) | | -7x4(x+12)=73 | | 24=14+2x | | 4x-12-2x=10 | | 12=3(d-14 | | -5x+4=-2x-5 | | 5c-7=2c+14 | | 2p+4=p+9 | | 9x-5=2x-3 |